ON THE SOURCES OF SAKKOKI’S LITERARY HERITAGE STUDY (Scientific journal of the Fergana State University, 2023)
This article summarizes information about the study of Sakkoki’s life and work. The article draws on the theoretical opinions of many literary critics and addresses them.We know very little about Mavlono Sakkoki, one of the founders of Uzbek poetry, who made significant contributions to Uzbek literature with his charming poems. It is worth mentioning that Sakkoki and his period, his literary activity, as well as his place in the Uzbek literature of the XV century are valuable works of Alisher Navoi’s "Majlis un-nafois", "Muhokamat ul-lug‘atayn", we can know the data.